STRATATEGI PENINGKATAN KUALITAS DOSEN DI PERGURUAN TINGGI - Sudiran, Sudiran (Jurnal Bestari, 1993)
Suharyadi, the general secretary of the Consultative Board of Private Universities, said that the quality of education would be better if teachers' and lecturers' welfare were improved. The statement seems logical. In Practice, however, is not so simple as that. Because there are many factors in the practice of teaching and learning process which affect the lecturers to achieve the instructional goals such as the background of lecturers, the background fo students, and the condition of campus as a place to transfer knowledge and technology.